SPORT NUTRITION KNOWLEDGE OF COACHES - Ivan Vasiljević; Danilo Bojanić; Jovica Petković; Aldijana Muratović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Decades of research support the theory that when there are sports competitions the question of what to eat and drink in order to enhance sport performance. Nutrition is one of the most important factors in achieving top performance athletes. According to most studies conducted in the world's top athletes receive information from their coaches when it comes to sports nutrition, especially of the coaches involved in fitness training. (Burns, Schiller, Merrick & Wolf, 2004).The aim of this study was to determine the knowledge of sports nutrition in sports coaching. Mthods: The sample was composed of 30 licensed coaches from Montenegro (football, handball, basketball, volleyball, athletics and tennis). Knowledge of sports nutrition was tested by means of a standardized questionnaire. The questionnaire was designed to determine the knowledge manager on sports nutrition, the ingredients that are necessary in order to provide a sufficient amount of energy to training and competition, the dietary supplements, meal prior to the competition as well as dehydration and rehydration during training and competition. The survey was anonymous. The data were analyzed by statistical methods, using the statistical software STATISTICA for WINDOWS. Results: According to the results as a whole, it can be concluded that the trainer's knowledge of sports nutrition at a satisfactory level. Out of 600 responses was achieved 469 correct answers, or 78.1%. However, when looking at individual responses then satisfaction with the relative high percentage loss since the observed large gaps on very important issues related to sports nutrition. Discussion: By analyzing and comparing research results (Matkovic, Prince & Cigrovski, 2006) that in a sample of 56 coaches basketball and skiing, received 77.8% of correct answers and insight into the results of our study, it is clear that the results of the approximate value of both work, which is an indicator of quality education trainers. However, viewing individual responses, worrying is the fact that one-third of respondents have very low levels of knowledge about protein supplements and believes that proteins are the main source of energy. If we take into account the fact that athletes are often used as a dietary supplement exactly as recommended by coaches, it would be expected that people advise taking these supplements know about any problems or negative occurrences that may endanger the health of athletes. References: Burns RD, Schiller R, Merrick MA, Wolf KN (2004). J Am Diet Assoc, 104, 246-9. Matkovic B, Knjaz D, Cigrovski V (2006). Croatian Sports Medicine Journal, 21, 3-7.